Determination of hydrology cycle in Universiti Malaysia Pahang (UMP) Gambang and Pekan campus - Ihsan, Md Yusoff (2017)
Climate change leads to changes in precipitation. This phenomenon has already begin to transform rainfall pattern in Malaysia. Rainfall data, temperature data, and evaporation data are collected and recorded monthly to display the relationship between rainfall, temperature, and evaporation to determine the pattern of hydrologic cycle. The relationship obtained, would also display the weather pattern at campus Universiti Malaysia Pahang (UMP) in Gambang and Pekan. Understanding the shift and predicting the changing trend in rainfall distribution is needed to manage floods. Changing trend in rainfall distribution also gives an effect on hydrological analysis especially related to historical rainfall record. Mann Kendall (MK) test and Sen's Slope estimator are employed to determine the rainfall trend of hydrologic cycle. The trend test would conclude if there is a rainfall trend or no rainfall trend at campus Universiti Malaysia Pahang (UMP) in Gambang and Pekan.